Análise de pesticidas organoclorados em água usando a microextração em fase sólida por headspace com cromatografia gasosa e espectrometria de massas - Prates,Crislaine Batista (2011)
A method based on headspace - solid phase microextraction coupled with gas chromatography - mass spectrometry was validated for the quantitative determination of 18 organochlorine pesticides in water. For the extraction conditioning some parameters as the best type of coating fiber, time and temperature of extraction, pH and ionic strength were evaluated. The method HS-SPME/GC-MS/MS showed linear coefficient above 0.9948. The repeatability of the measurements were lower than 7.6%. Relative recoveries were between 88 and 110%. Limits of detection from 0.5 x 10-3 to 1.0 mg L-1 were obtained. A total of 31 samples were analyzed and 16 presented from 1 to 5 pesticides.